2014
DOI: 10.1039/c4dt00309h
|View full text |Cite
|
Sign up to set email alerts
|

C–H and C–O bond activation with a rhodium(i) β-diiminate complex

Abstract: Complex LRh(COE) [L = (2,6-Me2C6H3NCMe)2CH; COE = cyclooctene] reacts with oxirane, methyloxirane and 2,2-dimethyloxirane to eventually produce LRh(COE)(CO) and alkane (methane, ethane, propane). This reaction and other aspects of the reactivity of the "LRh" fragment (hydrogenation of olefins and benzene) have been studied by density functional theory. The results indicate that for 2,2-dimethyloxirane (and probably also for methyloxirane) the reaction starts with C-H activation of a methyl group, followed by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…437 On the basis of DFT analysis at the PCM (MeCN) B3LYP/6-31G(d,p)(SDD) level of theory, the presence of σ-donating ligands such as phosphines was shown to be essential for 438 DFT calculations showed that oxirane was opened via C−O activation, whereas dimethyloxirane reacted via methyl C−H activation because of steric hindrance in the C−O activation pathway. Furthermore, the high catalytic activity of Rh was attributed to the good stabilization and balance between Rh(I) and Rh(III) oxidation states.…”
Section: Conjugate Additionmentioning
confidence: 99%
“…437 On the basis of DFT analysis at the PCM (MeCN) B3LYP/6-31G(d,p)(SDD) level of theory, the presence of σ-donating ligands such as phosphines was shown to be essential for 438 DFT calculations showed that oxirane was opened via C−O activation, whereas dimethyloxirane reacted via methyl C−H activation because of steric hindrance in the C−O activation pathway. Furthermore, the high catalytic activity of Rh was attributed to the good stabilization and balance between Rh(I) and Rh(III) oxidation states.…”
Section: Conjugate Additionmentioning
confidence: 99%
“…This metal-catalyzed cyclization yields the η 1 ,η 1 square-pyramidal complex INT 18 through a high-energy barrier of 34.2 kcal/mol, generating the requisite bicyclic ring system. From Rh complex INT 18 , the aromatization sequence proceeds via C–O bond activation of the dative methoxy group ( TS 18-19 ) leading to Rh­(IV) methoxy complex INT 19 via a turnover-limiting barrier of 44.4 kcal/mol, which is much higher than the barrier to alkyne insertion at TS 6a-7a or TS 9b-10b . Intramolecular deprotonation via TS 19-20 yields methanol complex INT 20 .…”
Section: Resultsmentioning
confidence: 99%
“…We have reported earlier on the synthesis of various ( Me BDI)Rh(olefin) complexes, with the olefins 1,5-cyclooctadiene (COD), norbornadiene, (C 2 H 4 ) 2 , norbornene, cyclooctene (COE), and 1,3-cyclohexadiene (CHD). , The first four of these show normal, static 1 H and 13 C NMR spectra. ( Me BDI)­Rh­(COE) exhibits fluxional behavior due to “ring walking” of the (BDI)Rh fragment via an olefin ⇆ allyl hydride equilibrium. , ( Me BDI)­Rh­(1,3-CHD) and ( Cl BDI)­Rh­(1,3-CHD) were reported to have partially broadened 1 H and 13 C NMR spectra at room temperature (sharp at −25 and −53 °C, respectively), but the nature of that fluxionality was never elucidated …”
Section: Resultsmentioning
confidence: 99%
“…Four-coordinate complexes typically prefer either a tetrahedral (TET) or a square-planar (SP) coordination geometry. The electron count is an important factor here: d 10 complexes tend to prefer a TET environment, whereas low-spin d 8 complexes are mostly SP. 1 Coordination environments can be fluxional, and in the case of SP complexes numerous examples are known where adjacent ligands switch place.…”
Section: ■ Introductionmentioning
confidence: 99%